Pengaruh Stres Kerja Terhadap Peningkatan Kinerja Karyawan pada PT. Multi Nabati Sulawesi Wilayah Luwuk Kabupaten Banggai - Syaiful Pakaya; Syamsul Syamsul; Idris Yunus (Journal of Technopreneurship on Economics and Business Review, 2021)
This study analyzes whether there is a significant influence on job stress on employee performance at PT. Multi Nabati Sulawesi Luwuk. The sample in this study was 57 employees, which then carried out random sampling. The sampling technique used in this study was random sampling. Simple regression analysis was used to test the hypotheses in this study. The results of this study indicate that the influence of the work stress variable (X) on employee performance (Y) is in a negative area. From the results of the t test, the value of t count = -1.609, while at the real level a = 0.05 and df = 56, it is obtained t table = 1.672. Because t count < t table with a probability of 0.113 is greater than 0.05, so it is proven that job stress has no significant effect on employee performance at PT. Multi Nabati Sulawesi Luwuk.